2002
DOI: 10.1177/002076402128783073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of a Psychiatric Intensive Care Unit: Is Ethnicity a Risk Factor for Admission?

Abstract: It is likely that a variety of factors contributed to the high rate of PICU admission amongst ethnic minority patients, including an increased prevalence of major mental illness and more frequent cannabis abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
2
12
2
Order By: Relevance
“…In contrast to recent studies conducted in London and the South East (Feinstein & Holloway, 2002;Brown & Bass, 2004;Pereira et al 2006), patients of black African/Caribbean ethnicity were not significantly more likely to be transferred to PICU compared with white patients. Similarly, patient ethnicity was not associated with seclusion, which conflicts with the findings of the Healthcare Commission investigation in which seclusion rates were higher among ethnic minority groups relative to white British patients (Healthcare Commission, 2005).…”
Section: Demographic and Clinical Predictors Of Treatmentcontrasting
confidence: 97%
“…In contrast to recent studies conducted in London and the South East (Feinstein & Holloway, 2002;Brown & Bass, 2004;Pereira et al 2006), patients of black African/Caribbean ethnicity were not significantly more likely to be transferred to PICU compared with white patients. Similarly, patient ethnicity was not associated with seclusion, which conflicts with the findings of the Healthcare Commission investigation in which seclusion rates were higher among ethnic minority groups relative to white British patients (Healthcare Commission, 2005).…”
Section: Demographic and Clinical Predictors Of Treatmentcontrasting
confidence: 97%
“…Similar conclusions were drawn in a previous study, conducted within the same NHS trust as that in the current investigation, which found that, although black African or Caribbean patients were more prevalent than expected (based on the ethnic composition of the entire hospital and the general population of the catchment area), black African or Caribbean PICU patients were characterised by higher levels of functional impairment than white PICU patients. 25 The current study extends these findings by statistically adjusting for a wide range of potential confounders, thereby demonstrating that these factors do indeed account for the higher likelihood of PICU transfer among black African or Caribbean patients.…”
Section: Predictors Of Use Of a Psychiatric Intensive Care Unit And Ssupporting
confidence: 69%
“…[24][25][26] This association between ethnicity and PICU status was greatly attenuated and rendered non-significant in the fully adjusted model. This finding is reassuring, as it suggests a lack of referral bias within the psychiatric inpatient system.…”
Section: Predictors Of Use Of a Psychiatric Intensive Care Unit And Smentioning
confidence: 94%
“…Of those that do, reported rates of unemployment are high, from 78% (Feinstein & Holloway 2002) to 100% (Cohen & Khan 1990). The latter study shows a significant difference with general patients, whose unemployment rate was 95.5%.…”
Section: Legal Statusmentioning
confidence: 99%